Pengaruh Penggunaan Beton Pracetak terhadap Penerapan Lean Construction pada Proyek Konstruksi di Manokwari dengan Pendekatan Systematic Literature Review (SLR) - Natalia E Safkaur (Journal of Engineering and Applied Technology, 2026)
This study aims to analyze the impact of precast concrete use on the implementation of Lean Construction in construction projects in Manokwari through a Systematic Literature Review approach. This study highlights the relationship between prefabrication-based construction technology and lean principles, which focus on reducing waste, improving time efficiency, and optimizing productivity and quality. Data were obtained from 25 scientific articles indexed in Scopus, ScienceDirect, and Google Scholar, published between 2015 and 2025, and analyzed using the PRISMA protocol. The synthesis results indicate that precast concrete can reduce material waste, shorten project duration, increase labor productivity, and produce more consistent work quality. The implementation of Lean becomes more effective when supported by a standardized precast system based on off-site production. In the context of Manokwari, this approach holds great potential for addressing logistical challenges and resource constraints, although it still faces infrastructure and initial cost barriers. These findings underscore the strategic role of precast concrete as a key enabler of Lean Construction in enhancing the performance of modern construction projects.